A importância da demonstração do valor adicionado como um instrumento para análise: um estudo da DVA dos bancos - Corsi, Darci Pereira (2016)
Statement of Value Added (SVA), is an accounting and financial report, required by law and legal for companies in the form of anonymous public companies, and large companies economic form of limited partnerships, and recommended to the other juridical types of companies, by regulators of accounting. The SVA was created from the inserter of Brazil in the international harmonization process of accounting information system, whose main goal is to qualify the information about business performance to users of accounting system, thus following the new conceptual framework of accounting, which in turn follows the economic global changes, social and business management. The Value Statement added, is based on information contained in the statement of income for the exercise, so that the revenues net of inputs acquired from third parties, and also deducted by the accounting adjustment expenses, in accordance with the basic assumption of competence produces the added value, which is the first part of the report, and thus producing the "GDP" of the business unit and the second part shows the distribution of this wealth to forming agents under the headings: staff salaries; government compensation through taxes, fees and contributions; payment of debt, through financial charges, rents and others; return on equity, through interest on equity, dividends and retained profit. The Statement of value added is an important tool in the accounting information system, which contributes to social and economic analysis of the company, producing indicators for the sector, region and the country. The paper describes the concepts and monetary training of all items report components, appraises the economic agents who participate in the formation and distribution of the wealth produced by a company, including reviewing the economic and legal aspects of a company. The paper presents the three models of the SVA presents an analysis of the added value produced by a company in the commercial sector, and one of the insurance industry, demonstrating the report's usefulness in economic and financial analysis of such companies, since they are economic entities, with different operating object and generate different nomenclatures for the items that underlie the preparation of the statement of value added. Finally the paper analyzes, through the statement of added value, the behavior of the allowance for doubtful accounts, the largest Brazilian financial institutions, which is a significant component in the composition of the spread, set by the Central Bank of Brazil